Effect of Intermediate Sheet Piles in Non-Homogenous Soil on Seepage Properties Under Hydraulic Structure Using SEEP/W Program - Asmaa A. Jamel (Tikrit Journal of Engineering Sciences, 2016)
The seepage through a permeable soil under hydraulic structure exerts uplift pressure and may carry soil particles there by leads to piping. This paper concerns to study the effect of using intermediate sheet pile under the apron of hydraulic structure besides the upstream and downstream piles rest on non-homogeneous soil layer. This configuration aim to show how it affect the uplift pressure, exit gradient and seepage discharge at toe of hydraulic structure by using computer program SEEP/W Package. From the software test carried out two cases, first case using two sheet pile one at the upstream and the other at the downstream, then compare its results with the second case when the sheet pile at upstream, downstream and intermediate pile introduced Also for each run the quantity of uplift pressure, exit gradient and discharge at toe of hydraulic structure were determined to develop an empirical equations. Also, the results have been verify with artificial neural network (ANN), this verification shown good agreement between them.